Comparison on Efficiency of Solid-Lubricant Fillers for Polyetheretherketone-Based Composites; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Panin S. V. Sergey Viktorovich; Nguyen Dyk An; Kornienko L. A.; Ivanova L. R.; Ovechkin B. B. Boris Borisovich (2018, 2018)
Title screen